The The Sustainable Development Paradigm through Carbon Tax Legal Construction - I Putu Gede Parwata; Ida Ayu Sadnyini (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
The purpose of this research is to answer legal issues related to the implications of the legal vacuum in the procedures for implementing a carbon tax and the formulation of fulfilling future a carbon tax obligations to provide certainty in the continuation of sustainable development. The legal research method used is normative juridical with a conceptual and statutory approach. The research results confirm that the implications of the legal vacuum in the procedures for implementing a carbon tax are related to threats to the sustainability of sustainable development. The threat in question is closely related to environmental damage due to significant climate change in the form of global warming and greenhouse emissions. The formulation of future a carbon tax regulations refers to the analogous legal construction method, namely regulating a carbon tax as well as a land and building tax and a value-added tax which emphasizes the importance of the state's role in regulating the behavior of business actors toward green economic activities that are lower in carbon. Apart from that, the role of the state, especially in mitigating climate change due to greenhouse emissions, requires financing expenditure. A carbon tax provides an opportunity to increase sources of state revenue and change the behavior of business actors to be more environmentally friendly.